Isolation and partial characterization of a protease with kallikrein-like activity from the egg-nests of hylesia metabus (crammer 1775) (Lepidoptera: Saturnidae), preliminary communication - Lundberg, Ulf; Osborn, Frances; Carvajal, Zoila; Gil, Amparo; Guerrero, Belsy; Arocha Piñango, Carmen Luisa (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Hylesia metabus is a species of moth, distributed principally in North Eastern Venezuela. Adult females use their abdominal hairs to cover and protect the eggs from predators and parasites. These hairs have urticating properties, causing a severe dermatitis in humans, whose symptoms worsen using soap and are alleviated by slightly acid substances e.g. vinegar. The hairs from male moths however do not produce any symptoms. In the present study we have isolated and partially characterized a protease with kallikrein-like activity from the female abdominal hairs of this species. Egg-nests (consisting mainly of female abdominal hairs) were collected from the twigs of mangrove-trees in affected areas after hatching. The proteic substances were extracted into Tris-buffered saline solution at pH 8.5, centrifuged, and chromatographed by size-exclusion chromatography (Sephadex G-75). Biological activity in the peaks was determined by amidolytic activity in the chromogenic substrates S-2288 (Broad Spectrum Serine Protease Substrate) and S-2302 (Kallikrein substrate). The eluates showing biological activity were concentrated by ultrafiltration and used for further analyses. The specificity in chromogenic substrates showed a preference for the kallikrein substrate S- 2302 followed by the broad-spectrum serine protease substrate S-2288. In addition the enzyme showed a pH optimum at pH 9, with no activity below pH 5. Thus the results of the present study support the hypothesis that this substance may be of importance in the lesions observed in individuals exposed to adult females or the egg-nests.